TH17/IL23 cytokine gene polymorphisms in bullous pemphigoid - Pardis‐Sadat Tabatabaei‐Panah; Hamideh Moravvej; Sahel Aghaei; Maryam Akbari; Sakineh Rajabi; Atena Kia; Elaheh Ebrahimi; Zahra Sadaf; Alireza Atoon; Nasim Behravesh; Ralf J. Ludwig; Reza Akbarzadeh (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background TH17/IL‐23 immune axis is considered to be involved in the pathogenesis of autoimmune and chronic inflammatory diseases. Bullous pemphigoid (BP) is the most frequent autoimmune blistering disease, characterized by the presence of autoantibodies against the components of the dermal‐epidermal junction. Animal studies and characterization of patient samples point toward a contribution of TH17 cells in BP pathogenesis. However, genetic polymorphisms in the genes of TH17/IL‐23 cytokines have not yet been well investigated in BP. Methods Detection of polymorphisms in IL‐17A (rs2275913 and rs3819025), IL‐17F (rs2397084 and rs763780), IL‐17RA (rs2229151), and IL‐23R (rs2201841, rs7530511, rs11209026, and rs10889677) genes were performed following the collection of blood samples and DNA extraction from BP patients and controls. Gene expression of IL‐23R was determined by quantitative RT‐PCR analysis. Results The prevalence of IL‐23R rs7530511 genotypes and alleles, as well as IL‐23R rs2201841 alleles, is significantly different between the BP patients and controls. While the minor C‐allele of IL‐23R rs7530511 is highly present in the patients, the G‐allele distribution of IL‐23R rs2201841 is significantly more prevalent in the control individuals compared to the BP patients. Genotypes and alleles of other SNPs in IL‐17A, IL‐17F, and IL‐17RA were similarly distributed in patients and controls. Conclusions No alteration was found in the gene expression between wild and polymorphic genotypes of IL‐23R (rs2201841 and rs7530511) variations, indicating they do not contribute to altering the levels of gene expression in blood. In summary, our data show that the alleles of two SNPs in IL‐23R rs2201841 and rs7530511 are associated with BP.